A ocorrência de moluscos transmissores da Esquistossomose mansônica no Córrego do Óleo e na Estação de Aqüicultura do Ibama em Uberlândia (MG) - Silveira, Elisângela de Paula (1997)
This work evaluates biological and epidemiologica features of B,O m p hahr,a breedmg sites in the municiplaity of Uberlândia, MO. The study was catried out tn the Corrego do óleo, an impottan stream located in the urban zone and w.theIBAMA s aquattc stafon to m October 93 to July 94 and to m October 95 to June 96 The stream was mapped and shared in sectors (A, B and C) and sections. The demarcai,on of secfons was by hnear meter o f stream at intervals of 100 meters and eaeh one was samples monthly. All fish breeding tanks of the IBAMA’s station were searched. The snatls were captured usmg sieves adapted with wooden handles and 10 Iadlefttls were taken eve,y 50 Imear metem c» dudpieu wiui w hv means of morphological and anatomical The Biomphalaria species were identifie y exnnsine the snaite tn features Schistosoma mansoni infection was investigated by exposing the snatls to vdiures. òcmsiosomu . , , kjoinoieal features of the Biomphalaria breeding artificial light. Physical, c e m ic a , . 10 s e c tions of the sector A. Monthly water sites were evaluated dunng six , turbity acidity and bicarbonate, chloride, samples were taken to analyse ^ P er^ regard from each section too. calcium and magnesium leveis. V ^ a s ite s a n d c a p tu r ed a total of 1.037 We identified 17 (32.0%) - s found in the sectors A and C.while snails in the Corrego do 01 _ _ S P g T h e s e pO pulations were alopatnc. In the B. straminea was recorded . settled by B. straminea only and ÍBAMA’s station we found I - e found in loth.c and l e U captured a total of 916 _ m ansoni. The statistical analysis indicated environments. No such snail wa d y c h e m ic a l parameters, except for chloride significant variances in ai p y e n v ironmental parameters showed significant concentration. Although none 0 greatest numbers of snails were taken in interference on Biomphalaria a u ' (October and November). The vegetation sections A3 and A10 and m ry re p re s e n tative plant families were Poaceae, comprised 36 plant species. ;nVertebrate fauna associated to Biomphalaria Cyperaceae and C o ^ e h ™CQã\ Unionidae and Ancylidae), turbellarions and included other mollusc (Lymn , COnclude that: the study area shows very annelids (Glossiphonidae and Nai £ B io m p ha laria breeding sites, as well as for suitable environmental conditions „ --cjnn Therefore, epidemiological monitoring becoming a focus of schistosomiasis ra in the surrounding area is necessary.